STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SEKOLAH DASAR - Slamet Sutoyo (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to determine; (1) Principal Strategy in improving teacher professionalism in 17 Rimau Island Elementary School; (2) implementation of the principal's strategy in increasing teacher professionalism, supporting and inhibiting factors in implementing the strategy at 17 Rimau Island Public Elementary School. This study used descriptive qualitative method. The technique of collecting research data was collected using observation and interview methods, the strategy of the principal in increasing teacher professionalism using several strategies; (1) Motivating teachers; (2) Growing discipline; (3) Awards; and (4) Guidance to teachers. Besides that, it also organizes and instructs teachers to take part in seminars and training, gives teachers the opportunity to continue their education, places teachers in the right proportion, gives rewards and welfare to teachers to improve performance, namely: first improving mental well-being by creating a school climate safe, peaceful, applying family principles. Supporting factors in the implementation of strategies namely physiology, security, affection, needs will be appreciated, and self-actualization. The inhibiting factors in implementing the strategy are; (1) not all teachers master the curriculum that is currently being used (2) there are still some teachers who have not been disciplined in teaching; and (3) there is an attitude of reluctance when they want to reprimand more teacherssenior compared to the principal.